(3eQGM GdCQhGMs - (3CHh GdaVGFd, MSGe GdOjf (B- (3UGMH GdnenQGM, CMeO Hf Ydj Hf eSYhO, J (B700 (3g`s ((3eMeO Hf eMeO Ydj GdfhQjs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3GYde Cf GdUQa Ce GdYdhe hGdfMh CHhgG hjbhj aj GdOQGjGJ OGQhgG hjWZi aj GdQhGjGJ YGQhgG aLeYJ ajg cJGHG ehSheG H (B... (3hgh ddUHj LfGM GdfLGM hQGM QMQGM haj eYOJg Mjf QGM eKd JaGM CQhGM (B...s
(3BNQgG (B:s
... (3hMce Yjfg cMc Whi aj GdJj GLJeY ajg EYdGdGf HJbOjQ EYdGdgeG haj GdJj de jLJeY GdEYdGdGf jchf McegG CjVG cMce Whi ddeJGHYI fMh WhjG hWGhjGf (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\175s
(3cTa GdXfhf (B2\1651s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdUQas